The Contribution of Foreign Real Estate Investment to Housing Price Growth in Australian Capital Cities. (14th July 2017) - Guest, Ross; Rohde, Nicholas
Abstract : This paper models the effects of foreign investment in real estate on housing prices in Australia. We use a variety of panel data models that account for cross‐sectional heterogeneity across Australian cities and find that increases in investment are significant predictors of rises in the Australian Bureau of Statistics' Residential Property Price Index. Our results are generally robust and suggest that increases in foreign investment account for between 20% and 30% of the rise in housing prices between 2004 and 2014 in Sydney and Melbourne. In other capital cities the effects appear to be negligible. Some policy implications of our findings are discussed.